Diversidade de fungos endofíticos do gênero Sarocladium em gramíneas - Anjos, Rafaela Merlo dos (2017)
Endophytic fungi are those that inhabit the interior of plants and do not cause apparent damage to their hosts. They can be found in leaves, stems and roots. During investigations on endophytic fungi of tropic grasses, the genus Sarocladium, belonging to the phylum Ascomycota, the Hypocreales order was the predominant one. The present project aimed to evaluate the morphological and phylogenetic diversity of endophytic fungi of the genus Sarocladium isolated from the grass species Brachiaria ruziziensis, B. brizantha, Panicum maximum, Penissetum purpureum and Cynodon nlemfuensis. For morphological characterization, the isolates were transferred to the OA and BDA media and incubated under two different temperatures, 25 ± 1 and 37 ± 1 ºC, in the dark. Colonial diameter, front and back staining, mycelial texture, and presence of exudate were examined after 2, 6, 10 and 14 days. Micro morphological characteristics were evaluated at day 14. Species identification was performed by molecular phylogeny using partial sequences of the ACT, ITS and LSU genes. Five phylogenetic species of Sarocladium were identified. S. terricola, with five isolates identified with ACT sequences, S. strictum, with two isolates identified using ACT and LSU, S. bactrocephalum, with three isolates identified with ACT and LSU and a probable new species with eight isolates. An isolate of S. hominis and one of S. kiliense were identified using ITS sequences. New analyzes will be needed to determine if the isolates of Sarocladium sp. Are species already known in the literature or will be characterized as one or more new species of Sarocladium.